Adolescent Risk-Taking Behaviors and School Performance: Distinguishing the Experiences of Boys and Girls - Lee Blair, Sampson (International Journal of Criminology and Sociology, 2017)
Previous studies have examined the risk-taking behaviors of adolescents and their impact upon a variety of outcomes, yet comparatively few have addressed educational consequences. Using a nationally representative sample of American high school seniors, this study examines how risk-taking behaviors are associated with school performance, and how this relationship may vary by gender. Framed within the life-course perspective, the analyses reveal that while adolescent boys engage in significantly higher levels of delinquency and substance use, the consequences of such behavior appear to be greater for girls. The implications of these findings are discussed, as well as the gendered nature of risk-taking.